2001
DOI: 10.1046/j.1471-4159.2001.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of neurotoxicity in cortical cultures and hippocampal slices from E2F1 knockout mice

Abstract: The E2F1 transcription factor modulates neuronal apoptosis induced by staurosporine, DNA damage and b-amyloid. We demonstrate E2F1 involvement in neuronal death induced by the more physiological oxygen-glucose deprivation (OGD) in mouse cortical cultures and by anoxia in mouse hippocampal slices. E2F1(1/1) and (2/2) cultures were comparable, in that they contained similar neuronal densities, responded with similar increases in intracellular calcium concentration ([Ca 21 ] i ) to glutamate receptor agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 31 publications
5
39
0
Order By: Relevance
“…E2F1 has been demonstrated to promote apoptosis in postmitotic neurons including cerebellar granule neurons (O'Hare et al, 2000;Gendron et al, 2001;Liu and Greene, 2001b). Consistent with these observations, we found that the dominant interfering form of E2F (E2F-Rb), when expressed in granule neurons, blocked the ability of KCl withdrawal to induce apoptosis (Fig.…”
Section: E2f Mediates Activity Deprivationinduced Cdc2 Transcription supporting
confidence: 87%
“…E2F1 has been demonstrated to promote apoptosis in postmitotic neurons including cerebellar granule neurons (O'Hare et al, 2000;Gendron et al, 2001;Liu and Greene, 2001b). Consistent with these observations, we found that the dominant interfering form of E2F (E2F-Rb), when expressed in granule neurons, blocked the ability of KCl withdrawal to induce apoptosis (Fig.…”
Section: E2f Mediates Activity Deprivationinduced Cdc2 Transcription supporting
confidence: 87%
“…It has been proposed that Cdk enzymes that normally regulate cell cycle progression in neurons may participate in the modulation of programmed cell death (Giardina et al, 1998;Hidetoshi and Chiba, 2001). This hypothesis is supported by previous studies in which the death of neurons, evoked by different stimuli such as serum and potassium deprivation (O'Hare et al, 2000;Martín-Romero et al, 2001;Trinh et al, 2001), excitotoxic treatment (Giardina et al, 1998;Park et al, 2000;Verdaguer et al, 2002b), and ␤-amyloid (Copani et al, 1999;Caricasole et al, 2003) and DNA damage agents (Gendron et al, 2001), is regulated, in part, by activation of cyclin-dependent kinases. Furthermore, there is evidence of the expression of cell cycle-related proteins in the brain of patients who have been suffering different neurodegenerative diseases (Jordan-Sciutto, 2002a,b;Yang et al, 2001Yang et al, , 2003.…”
Section: Discussionsupporting
confidence: 71%
“…Increasing OGD duration to 100 min in a similar mixed culture also did not give rise to any propidium-stained apoptotic cells [56]. Studies utilising caspase activation as an indication of apoptotic cell death, have also failed to demonstrate any increases in activity after either 60 [53] or 150 min [57] exposure to OGD. Another study which analysed apoptotic cell death using TUNEL combined with morphological analysis after 30-90 min exposure to OGD, found only a tiny proportion of the cells (0.05 %) underwent apoptosis by 48 h [58].…”
Section: Discussionmentioning
confidence: 89%